1976
DOI: 10.1126/science.959820
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[ a ]pyrene Diol Epoxides as Intermediates in Nucleic Acid Binding in Vitro and in Vivo

Abstract: Evidence has been obtained that a specific isomer of a diol epoxide derivative of benzo(a)pyrene, (+/-)-7 beta,8alpha-dihydroxy-9alpha, 10alpha-epoxy-7,8,9,10-tetrahydrobenzo(a)pyrene, is an intermediate in the binding of benzo(a)pyrene to RNA in cultured bovine bronchial mucosa. An adduct is formed between position 10 of this derivative and the 2-amino group of guanine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
220
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 565 publications
(225 citation statements)
references
References 11 publications
5
220
0
Order By: Relevance
“…Recently, in the process of BP-induced carcinogenesis, BP-diolepoxide has been implicated as the ultimate carcinogen since it appears as a conjugate of nucleic acids when BP is incubated with cells in culture (19)(20)(21)(24)(25)(26)(27). Osborne et al (26) found that both anti-and syn-BP-diolepoxide isomers react readily with DNA, yielding similar products.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, in the process of BP-induced carcinogenesis, BP-diolepoxide has been implicated as the ultimate carcinogen since it appears as a conjugate of nucleic acids when BP is incubated with cells in culture (19)(20)(21)(24)(25)(26)(27). Osborne et al (26) found that both anti-and syn-BP-diolepoxide isomers react readily with DNA, yielding similar products.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that BP is metabolized in cells to the 7,8-dihydrodiol which is a precursor to the 7,8-dihydrodiol-9,10-epoxide (BPDE) that reacts with cellular DNA. The BPDE bound mainly to guanine residues of DNA (Weinstein et al, 1976). The diol epoxides of DMBA and DB(a,l)P bind extensively to adenine residues of DNA (Cheng et al, 1988;Ralston (Burdette, 1955).…”
Section: Metabolism Of Pahs and Binding To Dnamentioning
confidence: 99%
“…There is circumstantial evidence that initial steps in chemical carcinogenesis with polycyclic aromatic hydrocarbons (PAH) involve metabolism to chemically reactive species by microsomal mixed-function oxidases (1) and the modification of nucleic acid bases by adduct formation (2)(3)(4)(5). Much of the recent work on PAH metabolism and carcinogenicity has focused on benzo [a]pyrene (BzP) and has led to the identification of many polar products of microsomal enzyme metabolism including the particularly reactive diol epoxide, BzP-7,8-diol-9,10-oxide (3), which accounts for most of the material covalently bound to DNA (2)(3)(4).…”
mentioning
confidence: 99%